Relationship between vertical and horizontal jump variables and muscular performance in athletes - Dobbs, C. W.; Gill, N. D.; Smart, D. J.; McGuigan, M. R. (The Journal of Strength and Conditioning Research, 2015)
This study investigated the relationship between vertical and horizontal measures in bilateral and unilateral countermovement jump, drop jump and squat jump (SJ), and sprinting speed and muscle architecture of both the vastus lateralis and gastrocnemius. Subjects (n = 17) completed a 30-m sprint test, muscle stiffness test; ultrasound measures, and a jump testing session. Measures of horizontal peak and mean force, in both bilateral and unilateral jumps, tended to have greater relationships to sprint speeds (R2 = 0.132-0.576) than peak and mean force in the vertical plane (R2 = 0.008-0.504). Vertical velocity variables also showed some large and very large correlations to sprint speed (R2 = 0.062-0.635). Unilateral measures of velocity tended to have larger correlations to sprint performance than their bilateral counterparts across all jump types and peak and mean velocity in SJ showed large and very large correlations to sprint speed (bilateral R2 = 0.227-0.635; unilateral 0.393-0.574). Few large correlations were shown between muscle stiffness measures of muscle architecture and kinetic and kinematic variables in either vertical or horizontal jumps. The present findings suggest that sport scientists and strength and conditioning practitioners concerned with the prognostic value of kinetic variables to functional movements such as sprint speed should also use horizontal jumps in addition to vertical jumps in testing and training.